Maize Combined Insect Resistance Genomic Regions and Their Co-localization With Cell Wall Constituents Revealed by Tissue-Specific QTL Meta-Analyses - Badji, Arfang; Otim, Michael; Machida, Lewis; Odong, Thomas; Bomet Kwemoi, Daniel; Okii, Dennis; Agbahoungba, Symphorien; Mwila, Natasha; Kumi, Frank; Ibanda, Angele; Mugo, Stephen; Kyamanywa, Samuel; et al. (Plant Science, 2018)
Combinatorial insect attacks on maize leaves, stems, and kernels cause significant yield losses and mycotoxin contaminations. Several small effect quantitative trait loci (QTL) control maize resistance to stem borers and storage pests and are correlated withsecondary metabolites. However, efficient use of QTL in molecular breeding requires a synthesis of the available resistance information. In this study, separate meta-analyses of QTL of maize response to stem borers and storage pests feeding on leaves, stems, and kernels along with maize cell wall constituents discovered in these tissues generated 24 leaf (LIR), 42 stem (SIR), and 20 kernel (KIR) insect resistance meta-QTL (MQTL) of a diverse genetic and geographical background. Most of these MQTL involved resistance to several insect species, therefore, generating a significant interest for multiple-insect resistance breeding. Some of the LIR MQTL such as LIR4, 17, and 22 involve resistance to European corn borer, sugarcane borer, and southwestern corn borer.
Keywords: Maize; Stem borers; Storage pests; Cell wall constituents; Tissue-specific meta-QTL; Multiple-insect resistance; Marker-assisted selection